مکالمہ بین المذاہب کا تجزیاتی مطالعہ - ڈاکٹر محمد ناصر; ڈاکٹر سید نعیم بادشاہ بخاری (Al Basirah, 2020)
Continues Scientific development made the world a global village , which brought different religions & civilizations closer to each other. This resulted in clash of civilization and differences among the followers of different religions. Sometimes these differences grow to the intensity which bring different followers in direct tussle and confrontation. So to bridge or minimize this gap some modern Muslim scholars have made efforts by using different slogans for this purpose, i.e. interfaith harmony, interfaith dialogue, unity of religions etc. and hold seminars , workshops and conferences almost all over the world. These efforts created queries in the minds of different peoples, whether difference of opinions is unlawful? Can we give up religious obligations for bringing all the people under the banner of this unity. The given article critically discusses the aims and motives behind these efforts; and draw a line of demarcation in Islamic perspective for creating harmony among the people of different religions and civilizations.